Systematic Literature Review: Implementasi Media Pembelajaran Assemblr Edu untuk Meningkatkan Hasil Belajar Siswa. - Widya Galih Prayoga; Parji; Supri Wahyudi Utomo (ASANKA : Journal of Social Science and Education, 2025)
This research is based on the importance of using innovative technology-based learning media to improve student learning outcomes, especially in facing the educational challenges of the Society 5.0 era. This study examines the effectiveness of implementing Assemblr Edu media in enhancing student learning outcomes across various academic levels. The method used is a Systematic Literature Review (SLR), analyzing 10 Sinta-indexed national journal articles published between 2021 and 2024. The results indicate that using Assemblr Edu effectively improves student learning outcomes, evidenced by increased average scores, completion percentages, and statistical significance. Its 3D visualizations and interactive features help reduce cognitive load and enhance understanding of abstract concepts, particularly in science subjects. In conclusion, Assemblr Edu is a universal and effective medium for various educational levels. This research recommends integrating Assemblr Edu with other models or media for optimal results. It suggests a need for in-depth identification of technical and non-technical obstacles in its implementation. This study provides an empirical foundation for developing technology-based learning strategies and innovative teaching practices in Indonesia. ABSTRAK Latar belakang penelitian ini didasari oleh pentingnya penggunaan media pembelajaran inovatif berbasis teknologi untuk meningkatkan hasil belajar siswa, terutama dalam menghadapi tantangan pendidikan di era Society 5.0. Tujuan penelitian ini adalah untuk mengkaji efektivitas penerapan media Assemblr Edu dalam meningkatkan hasil belajar siswa pada berbagai jenjang pendidikan. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan menganalisis 10 artikel jurnal nasional terindeks Sinta yang terbit antara tahun 2021–2024. Hasil penelitian menunjukkan bahwa penggunaan Assemblr Edu efektif dalam meningkatkan hasil belajar siswa, terbukti dari peningkatan nilai rata-rata, persentase ketuntasan, dan signifikansi statistik. Visualisasi 3D dan fitur interaktifnya mampu mengurangi beban kognitif dan meningkatkan pemahaman konsep abstrak, khususnya dalam mata pelajaran IPA. Kesimpulannya, Assemblr Edu merupakan media yang universal dan efektif untuk berbagai jenjang pendidikan. Penelitian ini merekomendasikan integrasi Assemblr Edu dengan model atau media lain untuk hasil yang lebih optimal, serta perlunya identifikasi mendalam terhadap kendala teknis dan non-teknis dalam implementasinya. Kontribusi penelitian ini memberikan landasan empiris bagi pengembangan strategi pembelajaran berbasis teknologi dan praktik pengajaran yang inovatif di Indonesia.